Data Deduplication in A Blockchain-Enabled Big Data Ecosystem: Secure and Efficient Cloud Storage - S. Seethalakshmi, Dr. B. Balakumar (South Eastern European Journal of Public Health, 2025)
To get around the limits of local storage and ensure that data can be accessed from anywhere at any time, cloud storage services have become very important. Data compression technology helps save bandwidth and disk space. Removing extra data from cloud storage can save up to 95% of room. Despite recent improvements in cloud storage, there are still security and privacy concerns. This piece discusses the security and privacy concerns related to big data and outlines the basic requirements that future solutions should address. This paper aims to introduce a new technology strategy for handling and controlling security and privacy risks related to big data. This paper uses a design science study method. The proposed system uses Blockchain technology to securely store large amounts of data by managing its information and rules and keeping outside parties out protecting data security and privacy. This method uses very little computing power to create file encryption keys. Tests and security checks show that it keeps the keys safe and protects the data's privacy. Computational speed improves because it takes less than 2 seconds to create encryption keys, even for a 500 MB file. We show a working model of our proposed system in a real-life data store scenario using the Ethereum Blockchain. The review and research show that our proposed framework provides a useful method for safely storing data in a Big Data environment.